Application of Raman spectroscopy in the hospital environment. Issue 4 (16th September 2022) - Pistiki, Aikaterini; Salbreiter, Markus; Sultan, Salwa; Rösch, Petra; Popp, Jürgen
Abstract: The hospital environment is a field with unique microbiological characteristics. Pathogens evolve and spread in different areas of the hospital affecting patients and staff. In addition, a constant circulation of pathogens between the hospital and the outer environment is ongoing. In this context, an extensive management is required in order to minimize the harmful effect of hospital flora on humans as well as the natural environment. Raman spectroscopy has been shown to be an effective tool for this purpose since it is applicable in a variety of biological samples ranging from the patient samples to the hospital's wastewater. It enables the detection of infection, bacterial species identification, antimicrobial resistance determination, epidemiological typing as well as infection control, mandatory for hospital management. The biggest advantages of this analytical method are the limited time and minimal resources required in its workflow. In the current review the Raman‐based analytical methods that have been developed over years in the field of microbiology are presented and their applicability in the different areas of the hospital environment is discussed. Abstract : The hospital environment has unique microbiological characteristics that require extensive management to avoid contamination of both humans and the natural environment. Label‐free Raman spectroscopy is an effective tool for this purpose with various applications ranging from infectious disease diagnostics over infection control to food and water safety. Here, Raman‐based analytical methods and their applicability in the different areas of the hospital environment are presented and discussed.